Further characterization of two sequiviruses infecting lettuce and development of specific RT-PCR primers - Jadao, A. S.; Krause-Sakate, R.; Liberti, D.; Pavan, Marcelo Agenor [UNESP]; Echer, M. M.; Svanella-Dumas, L.; Zerbini, F. M.; Candresse, T.; Le Gall, O. (Springer, 2007)
Lettuce mottle virus (LeMoV) and dandelion yellow mosaic virus (DaYMV) infect lettuce in South America and Europe, respectively. LeMoV and DaYMV possess isometric particles, occur at low concentrations in plants and have narrow host ranges. Partial genome sequences of both viruses were obtained using purified viral preparations and universal primers for members of the family Sequiviridae. DaYMV and LeMoV sequences were analyzed and showed identity with other members of the family. Universal primers that detect both viruses and specific primers for LeMoV and DaYMV were designed and used in RT-PCR-based diagnostic assays. These results provide the first molecular data on the LeMoV and DaYMV genomes and suggest that LeMoV is a member of the genus Sequivirus, probably distinct from DaYMV.